Shield behavior in multi-layer ground - Parameswaran, Y.; Sugimoto, M.; Nopodol Phein-wej; Bergado, Dennes T.; The Government of Norway (Bangkok : Asian Institute of Technology, 1996)
This research study is confined with developing a three dimensional Simulator of a cylindrical shield in multi-layered ground based on analytical formulation taking account of self weight, buoyancy, jack force, ea1th pressure distribution on cutter face which is function of velocity of shield and rotational speed of cutter face, and the earth pressure distribution on skin plate which is function of displacement of soil. By considering the equilibrium conditions of all these forces and moments, the displacement, rotation of shield and the mobilized coefficient of friction is determined. The Modified Marquart method of optimization is used for solving the non-linear equations. To determine the actual stress distribution on cutter face and skin plate , it is divided into a number of small elements. The required number of elements and the time interval between two successive steps is investigated from the excavated area. At each steps, the layer number corresponding to each calculation point is determined by position vector of each point. From this research, it has been found that shield is behave as unsteady state when it is in multi-layered ground and it becomes to steady state when the whole pait of shield goes into the single layer. To investigate the influence of various parameter, the sensitivity analysis is carried out by fixing all input parameters except only one parameter as variable. The over all scheme of analysis is done by developing a computer program coded in FORTRAN 77.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Engineering, School of Civil Engineering
Thesis (M. Eng.) - Asian Institute of Technology, 1996
Keywords: Shields (Geology)